POTENSI DAN PENINGKATAN INVESTASI DI SEKTOR PERTANIAN DALAM RANGKA PENINGKATAN KONTRIBUSI TERHADAP PEREKONOMIAN DI PROVINSI BALI - Suyana Utama, Made (Buletin Studi Ekonomi; Vol 18, No. 1,Februari 2013. (PP 1-84), 2013)
World Food Security Summit held in November 2009 produced a commitment to increase investment in agriculture and eliminating hunger sooner than originally targeted, as well as to reduce poverty and food security for the community. Consistent with the policy of autonomy, in order to develop the agricultural sector investments, then each area is expected to attract as many investors are willing to invest for the development of their respective regions.
Keywords: potency, investment, agriculture, regional autonomy